Respostas
respondido por:
10
a3 = a1 + 2r
a7 = a1 + 6r
a1 + 2r + a1 + 6r = 100
2a1 + 8r = 100
a1 + 4r = 50 => a1 = 50 - 4r
a4 = a1 + 3r
a11 = a1 + 10r
a1 + 3r + a1 + 10r = 150
2a1 + 13r = 150
2 . (50 - 4r) + 13r = 150
100 - 8r + 13r = 150
5r = 150 - 100
5r = 50
r = 10
a1 = 50 - 4r
a1 = 50 - 4.(10)
a1 = 50 - 40
a1 = 10
a7 = a1 + 6r
a1 + 2r + a1 + 6r = 100
2a1 + 8r = 100
a1 + 4r = 50 => a1 = 50 - 4r
a4 = a1 + 3r
a11 = a1 + 10r
a1 + 3r + a1 + 10r = 150
2a1 + 13r = 150
2 . (50 - 4r) + 13r = 150
100 - 8r + 13r = 150
5r = 150 - 100
5r = 50
r = 10
a1 = 50 - 4r
a1 = 50 - 4.(10)
a1 = 50 - 40
a1 = 10
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás